A robust and scalable active-matrix driven digital microfluidic platform based on printed-circuit board technology. Issue 10 (7th April 2021) - Xing, Yaru; Liu, Yu; Chen, Rifei; Li, Yuyan; Zhang, Chengzhi; Jiang, Youwei; Lu, Yao; Lin, Bingcheng; Chen, Peizhong; Tian, Ruijun; Liu, Xianming; Cheng, Xing
Abstract : An active-matrix digital microfluidic platform based on printed-circuit board technology is developed as a robust, highly scalable, low cost, easy to use, and contamination-insensitive device for automatic and parallel droplet handling. Abstract : Two-dimensional digital microfluidic platforms, on which droplets are actuated by electrowetting on dielectrics, have merits such as dynamic reconfigurability and ease for automation. However, concerns for digital microfluidic platforms based on low-cost printed circuit boards, such as the scalability of the electrode array and the reliability of the device operation, should be addressed before high throughput and fully automatic applications can be realized. In this work we report the progress in addressing those issues by using active-matrix circuitry to automatically drive a large electrode array with enhanced device reliability. We describe the design and the fabrication of a robust and scalable active-matrix driven digital microfluidic platform based on printed-circuit board technology. Reliable actuation of aqueous and organic droplets is achieved using a free-standing double-layer hydrophobic membrane. To demonstrate the versatility of the digital microfluidic platform, a pentapeptide is synthesized on the device within 30 minutes. With these improvements, a fully automatic, scalable, robust, reusable, and low-cost digital microfluidic platform capable of parallel manipulation of a large number of droplets can find numerous applications in chemical engineering, bioengineering and biomedical engineering.